Development of Bioactive Glass-Collagen-Hyaluronic Acid-Polycaprolactone Scaffolds for Tissue Engineering Applications - Zurita-Méndez, N. N.; Carbajal-De la Torre, G.; Flores-Merino, M. V.; Espinosa-Medina, M. A. (Frontiers in Bioengineering and Biotechnology, 2022)
In this work, bioactive glass (BG) particles synthesized by a sol-gel method, hyaluronic acid (HYA) and collagen (COL) extracted from chicken eggshell membranes (ESM) and as-purchased polycaprolactone (PCL) were used to obtain a novel bioactive scaffold using the gel-pressing technique. Two composites mixtures in weight percent were obtained identified as: SCF-1 and SCF-2, and were characterized by using FTIR, XRD, and SEM techniques. Subsequently, the composite materials applied as coatings were evaluated in simulated body fluid solutions using electrochemical techniques. The results of bioactivity and biodegradability evaluations, carried out by immersing in simulated body fluid and phosphate-buffered saline solution, showed that the SCF-1 sample presented the best biocompatibility. In accordance with the potentiodynamic results, the 316L-SS and the SCF-1 coated SS showed a very similar corrosion potential (Ecorr), around the -228 mV, and current density (icorr) values in close proximity. While, the SCF-2 coated SS showed more positive Ecorr around -68 mV, and lower icorr value in one order of magnitude. These results agree with those obtained by electrochemical impedance spectroscopy, which show a corrosion mechanism governed by activation and finite diffusion through the porous layer. In addition, results were complemented by dynamic compression testing under oscillating forces to identify the developed scaffolds' response under external forces, where the SCF-1 scaffold presented a maximum compression. The degradation resistance, bioactivity, and mechanically obtained measurements, provided interesting results for potential further studies in tissue engineering.